Contribution of chromosomal abnormalities and genes of the major histocompatibility complex to early pregnancy losses - Tkach, I.R.; Sosnina, K.O.; Huleyuk, N.L.; Terpylyak, O.I.; Zastavna, D.V.; Weise, A.; Kosyakova, N.; Liehr, T. (2015)
Aim. The determination of chromosomal abnormalities in samples from early pregnancy losses and allelic polymorphism of HLA–DRB1 and DQA1 genes in couples with recurrent miscarriage. Methods. Banding cytogenetic and interphase mFISH analysis, DNA extraction by salting method, PCR, agarose gel electrophoresis. Results. Cytogenetic and molecular-cytogenetic investigations of SA material identified karyotype anomalies in 32.4 % of cases with prevalence of autosomal trisomy – 42.65 %, triploidy – 30.38 % and monosomy X – 19.11 %. Complex analysis of frequency and distribution of allelic variants of genes HLA-DRB1 and HLA-DQA1 allowed establishing the alleles DRB1*0301, DRB1*1101-1104 and DQA1*0501 to be aggressor alleles in women with recurrent pregnancy loss (RPL). The cumulative homology of allelic polymorphism of more than 50 % of HLA-DRB1 and HLA-DQA1 loci between partners increases the risk of RPL by almost four times. Conclusion. The detected chromosome aneuploidies in the samples from products of conception and the changes in the major histocompatibility complex genes can cause the failure of a couples reproductive function and can lead to an early fetal loss.